Identification of Tourism-Based MSME Marketing Management Strategies - Hermawan, Romy; Supriono, Supriono; Rizaldi, Rasyid Akbar; Sudarmiatin, Sudarmiatin (Indonesia Marketing Association (IMA), 2024)
Sugihwaras Village is a village located in Ngancar District, Kediri Regency. The Sugihwaras Village area includes plantation areas, forestry areas and the Mount Kelud Tourism Area, which means that some economic activities take place in the agricultural and tourism sectors. A well-known agricultural commodity is pineapple with a typical mainstay product, namely